Revolutionizing Healthcare: A Comprehensive Review of Metaverse Integration for Enhanced Patient Outcomes, Medical Practices, The Potential Applications, Challenges and Future Direction - Ahmad Anwar bin Zainuddin; Muhammad Hafiz Faruqi Md Saifuddin; Wan Muhammad Arif Wan Azman; Abdul Ghafur Fuadi; Ahmad Adam Nadzeeran Ahmad Nadzri; Muhammad Hussaini Mohamad Fadil; Nuramiratul Aisyah Ruzaidi (PT. Visi Media Network, 2024)
Integrating the Metaverse into the healthcare system can significantly improve patient outcomes, medical education, and healthcare practices. This study examines the various uses of the Metaverse, emphasizing the essential technologies that make it possible, such as Augmented Reality (AR), Virtual Reality (VR), Extended Reality (XR), and digital twins for personalized care. The report highlights the challenges that healthcare professionals may face while suggesting future paths in the healthcare field. Topics examined include telemedicine, medical education, and the potential advancements that can be achieved with AR, VR, XR, and digital twins. Notable uses encompass virtual counseling, medical training and education, digital therapeutics, and telemedicine. While integrating the Metaverse into healthcare can significantly enhance patient care, it may pose privacy and security risks, incur high costs, require legal compliance, and affect trust in patient-technology relationships. However, future trends should address security and legal issues, balance social and virtual life, and enhance medical training and education. By using augmented reality (AR), virtual reality (VR), extended reality (XR), and digital twins, the healthcare industry can improve patient communication, research and decision-making processes, remote healthcare services, precise medical education training, and tailored patient care. These technologies present a unique opportunity to transform healthcare while addressing privacy, security, and sustainability issues. The purpose of this paper is to review the topic comprehensively, provide suggestions for future research and advancement in this domain, and provide insights into the potential of the Metaverse to revolutionize healthcare.